Prevalance of Brucellosis In etiology of low back pain In Elazig region - Erol, Fatih S.; Kizirgil, Ahmet; Topsakal, Cahide; Özveren, M. Faik (Fırat University, 2001)
Prevalence of Brucellosis in patients with low back pain and radicular symptoms in regard with unpasteurized use of milk and its products in this region was investigated. In 18 patients out of 1726 (1.04%) applied to Neurosurgery Clinic, Medical School, Firat University, with low back and/or leg pain for 18 months, brucellosis were diagnosed using brucella aglutination test. In this study, it was found that brucellosis did not showed typical clinical symptoms as usual and that six patients had no complaints apart from low back or leg pain. In conclusion, we suggest that brucellosis should not be ignored, even though there is no apparent clinical symptoms, in the etiology of radicular symptoms encountered in the region.

Yöremizde pastorize edilmeden hazırlanan süt ve süt ürünlerinin tüketimi dikkate alınarak bel ağrısı veya radiküler semptomları olan hastalarda bruselloz sıklığı araştırıldı. Fırat Üniversitesi Tıp Fakültesi Nöroşirürji Anabilim Dalı' na 18 aylık süre içinde bel ve/veya bacak ağrısı yakınması ile başvuran 1726 hastanın 18' inde (%1.04) brusella tüp aglutinasyon testi ile bruselloz saptandı. Bu çalışmada, brusellozun tipik klinik semptomlarını her zaman göstermediği, altı hastanın bel veya bacak ağrısı dışında hiçbir yakınmasının olmaması dikkat çekti. Yöremizde rastlanan radiküler semptomların etyolojisinde belirgin klinik semptomları olmasa dahi brusellozun gözardı edilmemesi gerektiği kanısına varıldı.
ELAZIĞ YÖRESİNDE BEL AĞRILARININ ETYOLOJİSİNDE BRUSELLOZ SIKLIĞI